Durable Effect of Radioactive Iodine in a Patient with Metastatic Follicular Thyroid Carcinoma - Aubrey A. Carhill; Rena Vassilopoulou-Sellin (Case Reports in Endocrinology)
Objective. Thyroid cancer is the most common endocrine malignancy and fastest increasing of all cancers in both men and women in the United States. Traditionally, differentiated thyroid cancer (DTC) carries a good prognosis when diagnosed early, but increasingly patients are presenting with late-stage disease and bone metastasis which carries a poor prognosis. Treatment of DTC involves surgical resection followed by radioactive iodine (RAI), which conventionally is thought to reach maximal effectiveness between 6 and 12 months following treatment. We report a case and review the literature surrounding long-term effect of radioactive iodine treatment in metastatic thyroid carcinoma. Methods. Patient clinical encounter and the literature review. Results. We describe a 49-year-old woman with symptomatic metastatic follicular thyroid cancer (FTC) to the spine and radiographic evidence of spinal cord compression who was effectively treated with RAI. Her initial serum thyroglobulin (Tg) levels following total thyroidectomy were 1,343 ng/mL which dramatically dropped to less than 100 ng/mL following RAI. Forty-three months following treatment with RAI, she has experienced complete resolution of her symptoms and continues to maintain persistently low-thyroglobulin levels of less than 100 ng/mL. Conclusions. RAI is believed to reach peak efficacy within 6–12 months; however, little has been reported regarding the long-term duration of benefit. This case demonstrates that the benefits of RAI therapy may be enduring, even in patients with widely metastatic thyroid cancer. It suggests in clinically stable patients with declining thyroglobulin after treatment, that there may not be an immediate need for additional therapy as RAI treatment may provide lasting effects.